FLUKS DAN DISTRIBUSI PARTIKEL ENERGETIK DI ORBIT LEO PENYEBAB TERJADINYA ANOMALI SATELIT - Nizam Ahmad; - Rasdewita K. (Jurnal Sains Dirgantara, 2010)
The variation of satellite anomaly caused by the impact of energetic particle depends on the energy and particle fluxes distributed on the region of satellite placement. The determination on fluxes and particle distribution in low earth orbit was done by analyzing the satellite anomaly cases from the year of 2000 until 2009 and using particle data from NOAA 15 satellite. The analysis gives information about 6 anomaly cases occurred at high latitude, 3 cases at mid latitude dan 12 cases at low latitude. Most satellite anomaly cases caused by proton and electron simultaneously, wherein the flux order about 104 up to 106 particles/cm3 and the energy, E > 30 keV for electron and 80 litlle than E litlle than 240 keV for proton. This analysis also shows most anomaly cases were occurred on polar satellite at 23 local time. Keywords: Satellite anomaly, Proton, Electron